Provocarea ilegală a avortului – o agresiune asupra vieții intrauterine [Articol] - Balcan, Silvia (CEP USM, 2022)
This article analyzes the pros and cons of abortion, which is considered a derogation from the right to life and has been the subject of discussion by researchers over time. The issue of legalization of abortions, including the permissible period of their performance, conditions a multitude of controversies regarding the fact if it is or not an absolute right of women, or an aggression against the human being during intrauterine development. The aim of this study is to identify legislative solutions both for ensuring the women right to reproductive health, and also for the protection of intrauterine life.
Keywords: abortion; right to life; product of conception; intrauterine life; illegal provocation of abortion